Planned Pregnancy in a Chronic Myeloid Leukemia Patient in Molecular Remission - Carolina Pavlovsky; Isabel Giere; Germán Van Thillo (Case Reports in Hematology)
Excellent response rates and a good quality of life have been observed since the introduction of tyrosine kinase inhibitors (TKIs) in chronic myeloid leukemia (CML) treatment. Consequently, some challenges began to appear in CML women in child-bearing age wishing to become pregnant. Currently, many women around the world are in stable major/complete molecular response MMR/CMR (MMR: <0.1% BCR-ABL/ABL and CMR: undetectable BCR-ABL mRNA by RQ-PCR transcript levels on the international scale). The condition of stable MMR/CMR is linked to a long-term virtual absence of progression to the accelerated and blastic phase and to the possibility of stopping the TKI treatment with the maintenance of a condition of CMR in a proportion of cases. Imatinib teratogenic and prescribing information prohibits the use of it during pregnancy. We describe the case of a 36-year-old female patient with CML in chronic phase who stopped imatinib after 2 years in major molecular response (MMR) to plan a pregnancy. Molecular monitoring by RQ-PCR was performed quarterly. She achieved a safe pregnancy and delivery maintaining an optimal molecular response throughout the pregnancy. Isolated literature reports have been described, but no formal advice has been described at present time.